2015
DOI: 10.1002/ccd.26168
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of chronic total coronary occlusions—high success rate despite a restrictive use of the retrograde approach

Abstract: A high CTO-PCI success rate of above 90% could be achieved with a restrictive use of the retrograde technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…After 2 years, the success rate of CTO-PCI greatly improved, reaching 90% in the third year [ 17 ]. In a study in 2016, a novice operator was observed for 5 years; when the retrograde utilization rate was only 18%, the operation volume of 80 cases/year was maintained, and the final success rate reached 90% [ 20 ]. A similar “inflection point” was found in a recent study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 years, the success rate of CTO-PCI greatly improved, reaching 90% in the third year [ 17 ]. In a study in 2016, a novice operator was observed for 5 years; when the retrograde utilization rate was only 18%, the operation volume of 80 cases/year was maintained, and the final success rate reached 90% [ 20 ]. A similar “inflection point” was found in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…At present, retrograde technology is recommended only in the antegrade technology, which is difficult to open and has a good side effect. The total success rate of CTO-PCI can be greatly improved with the improvement in the success rate of antegrade technology [ 20 ]. Finally, based on previous findings, the consensus of the European CTO club, and the situation of the center, the implementation period of ≥5 years and the annual operation volume of ≥60 cases were selected as the threshold of operator experience division, and the success rate of ≥90% was used to divide “experts” and other operations.…”
Section: Discussionmentioning
confidence: 99%